2012
DOI: 10.2118/141145-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Scale Inhibitors in Marcellus High-Iron Waters

Abstract: The Marcellus waters of Pennsylvania and West Virginia commonly contain elevated levels of calcium, barium, and iron. Theoretical analyses of these waters indicate a propensity toward the formation of calcium carbonate, barium sulfate, strontium sulfate, and iron-related scales. The high level of dissolved iron commonly present in the water adversely affects the ability of the scale inhibitor to inhibit calcium carbonate scale. In this study, the inhibition performance of two new chemicals and some commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Other species are formed at various pHs: HSO4 -, H + and SO4 2-. The problem is further complicated by the presence of metal ions like Fe and Al etc which can have a further negative impact on scale inhibitor performance 5,6 . The sulphuric acid molecule has two Hydrogen atoms (protons) and can therefore donate one proton to form HSO4or both of them to form SO4 2-.…”
Section: Dissociation Of Sulphate and Bi-sulphate At Low Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species are formed at various pHs: HSO4 -, H + and SO4 2-. The problem is further complicated by the presence of metal ions like Fe and Al etc which can have a further negative impact on scale inhibitor performance 5,6 . The sulphuric acid molecule has two Hydrogen atoms (protons) and can therefore donate one proton to form HSO4or both of them to form SO4 2-.…”
Section: Dissociation Of Sulphate and Bi-sulphate At Low Phmentioning
confidence: 99%
“…The use of membranes is increasingly being adopted for treatment of these waters, however, there is potential for rapid fouling and scaling if the right antisclants are not used to prevent crystallization. Furthermore, the scaling problem is complicated by the presence of metal ions like Fe and Al and impurities which may render the traditional antiscalant to become ineffective 5,6 . A series of experiments were performed to assess calcium sulphate scale formation and inhibition in the presence of metals at low pH.…”
Section: Introductionmentioning
confidence: 99%
“…Scale inhibitors have been applied successfully to prevent the formation of different scales where they act either as chelating agents to form a soluble complex, as threshold inhibitors, which block the development of the supercritical nuclei or as retarders of the growth of the scale crystals (Raju 2009, Amjad 1994, Shen et al 2012, Kan et al 2009). Various calcium sulfate scale inhibitor classes were used to mitigate the calcium sulfate precipitation: poly phosphates, organophosphorus compounds, and polymeric inhibitors.…”
Section: Theorymentioning
confidence: 99%
“…, have limited applications in oilfield industry and they are mainly used in boiler water treatments at low calcium concentrations(Fan et al 2010, Farooqui 2014, Shen et al 2012,Kan et al 2009). Another type of calcium sulfate scale inhibitors is organophosphorus compounds.…”
mentioning
confidence: 99%
“…adopted citrate to sequestrate iron and found that the presence of citrate could significantly improve inhibitor performance. These authors attributed the reason to be the prevention of the formation of iron carbonate seed particles, which can promote scale crystal growth in the brine …”
Section: Introductionmentioning
confidence: 99%